Detection of drug-resistant Salmonella serovars and absence of Listeria in the associated organic farm environment - RAUTELA, R; MAANSI; RAWOOL, D B; UPADHYAY, A K; KUMAR, DEEPAK; SINGH, D K; TEWARI, A K; RAUTELA, A; PARMAR, T (The Indian Journal of Animal Sciences, 2024)
The study was carried out to investigate two important foodborne pathogens, Salmonella and Listeria spp. in five organic farms in Uttarakhand state in the year 2018. The samples from soil, manure, water, and plants/plant parts were collected and screened for pathogens. The covered isolates were assayed for their antimicrobial susceptibility and the presence of representative beta-lactamase antibiotic-resistant gene (ARG) by PCR. A total of 2.2% (11/500) of samples tested positive for the genus Salmonella. However, none of the samples tested positive for Listeria spp. All the Salmonella isolates were recovered from environmental sources. On serotyping, 4 isolates were identified as serogroup Group C1, 3 as Salmonella Miyazaki, 2 as Salmonella Virchow and 1 each as Salmonella Infantis and Salmonella Gabon. Two Salmonella isolates, belonging to S. Group C1 and one S. Miyazaki isolate were pan-susceptible to all the antibiotics tested, while S. Virchow and S. Infantis showed multidrug-resistant. On PCR screening for three β-lactamase resistant genes (blaCTX-M-9, blaTEM, and blaAmpC), only three S. Miyazaki isolates amplified the blaCTX-M-9 gene. The study highlights the presence of MDR Salmonella in the organic farm environment warranting further studies in this direction to ensure safe organic farm produce for consumers.